Society of the dead : Quita Manaquita and Palo praise in Cuba - Ochoa, Todd Ramón, 1969- (University of California, 2010)
In this first-person account, Todd Ramón Ochoa explores Palo, a poorly-understood Kongo-inspired 'society of afflication' at the margins of Cuban popular religion. Narrated as an encounter with two teachers of Palo, the book unfolds on the outskirts of Havana.